Impact of chronic obstructive pulmonary disease on mortality in elderly patients with hip fracture: A retrospective cohort study - Jiaxuan Zhu; Yu Chang; Xiaomin Wang; Yuying Li; Fan Yang; Yuwei Shi; Xiuguo Zhang (PLoS ONE, 2026)
Objective Chronic obstructive pulmonary disease (COPD) is thought to increase mortality risk in elderly patients with hip fracture, but its independent effect remains unclear. This study aimed to determine whether COPD is an independent predictor of mortality in this population. Methods A retrospective cohort study was conducted on elderly patients with hip fractures. Through propensity score matching, confounding factors between patients with chronic obstructive pulmonary disease (COPD) and those without COPD were balanced. LASSO and Cox regression methods were used to identify predictors of mortality. The performance of the model was evaluated via ROC curves, calibration curves, and decision curve analysis. Restrictive cubic spline analysis and subgroup analysis were also performed to assess nonlinear effects and interactions. Results A total of 151 (11.08%) of the 1362 participants who were enrolled in the trial had COPD. After PSM, 537 data points were analysed. The COPD group presented a significantly greater incidence of postoperative respiratory failure (6.04%) and delirium (12.08%) and significantly greater 1-year mortality (22.82% vs. 5.93%). COPD was identified as a strong independent predictor of mortality (HR 7.291, 95% CI: 3.619 ~ 14.691). Other independent risk factors included age (HR 1.066, 95% CI: 1.016 ~ 1.118), HCT (HR 0.922, 95% CI: 0.872 ~ 0.975), CAR (HR 1.476, 95% CI: 1.209 ~ 1.801), and BNP (HR 1.001, 95% CI: 1.000 ~ 1.001). The prediction model showed good predictive efficiency, achieving an AUC of 0.834 (95% CI: 0.766, 0.902) in the training set and 0.892 (95% CI: 0.819, 0.965) in the validation set. Restricted cubic splines confirmed linear relationships between continuous predictors and mortality risk (all P values for nonlinearity > 0.05). Subgroup analysis revealed a significant interaction effect between sex and COPD (p = 0.028). Conclusions COPD is a strong independent risk factor for 1-year mortality in elderly hip fracture patients. The developed prediction model can help clinicians identify high-risk patients early and implement personalized management strategies.